Bridges and barriers: religion and immigrant occupational attainment across integration contexts - Connor, Phillip; Koenig, Matthias (International migration review, 2013)
This article advances knowledge about context-dependent impacts of religion on immigrant structural integration. Drawing on theories of inter-generational immigrant integration, it identifies and spells out two context-dependent mechanisms through which religion impinges upon structural integration — as ethnic marker prompting exclusion and discrimination, or as social organization providing access to tangible resources. The propositions are empirically tested with nationally representative data on occupational attainment in three different integration contexts which vary in religious boundary configurations and religious field characteristics — the United States, Canada, and Western Europe. Using data from the US General Social Survey, the Canadian Ethnic Diversity Survey, and the European Social Survey, the article analyzes indirect and direct effects of religious affiliation and participation on occupational attainment among first and second generation immigrants. The analyses find only limited evidence for the assumption that in contexts with strong religious boundaries (such as Western Europe and, to a lesser extent, Canada), immigrants face religious penalties in structural integration. By contrast, the analyses support the assumption that in contexts with a thriving religious field (such as the United States and, to a lesser extent, Canada), religious attendance tends to be positively related to occupational attainment, especially for the second generation. For the first time, the article empirically tests arguments about transatlantic differences in the role of religion for immigrant structural integration, and it suggests ways of better integrating micro-oriented survey research with macro-oriented institutional analysis.